Corporate social responsibility and corruption risk: A global perspective. Issue 1 (April 2018) - Krishnamurti, Chandrasekhar; Shams, Syed; Velayutham, Eswaran
Abstract: This paper extends our knowledge on corporate corruption risk by examining whether and to what extent corporate social responsibility (CSR) affects firm-level corruption risk. Using a cross-country sample of major multinational firms, we find that firm-level CSR mitigates corruption risk. On closer examination, we find that the relationship between CSR and corruption risk is mediated by country-level variables such as institutional quality, protection of minority shareholders' rights, stock market development and freedom of the press. Further, we find that in emerging countries, CSR mitigates corruption risk only when the country-level institutional quality is high and citizens enjoy press freedom. Our findings suggest that both formal institutions and the quality of civil society influence the effect of CSR on corruption risk. Our results remain robust to controls for endogeneity and potential sample selection bias.